Total phenolic content, flavonoid concentration and antioxidant activity of indigenous herbs, physalis minima linn - Helling, Mealianny (2019)
Physalis minima linn is a plant that listed under the family of Solanaceae that has many biological effects such as antioxidant activity that is good for health. However, it is not widely used in medicinal area. Antioxidant is important to be supplied to our body such that it acts as inhibitor to inhibit the free radical formed. Free radical formed due to oxidation process which take place in our body leading to formation of reactive oxygen species having free radical. Thus, the objective of this research is to determine the total phenolic and total flavonoid content of Physalis minima linn besides to evaluate the antioxidant activity of different parts (whole plant, leaves, stem, fruit, and root) of the plant. The total phenolic content and total flavonoid content of Physalis minima linn are determined by using Folin-Ciocalteu method and aluminium chloride colorimetric assay, respectively while antioxidant activity is determined by using DPPH assay. It was analyzed that leaves extract had the highest total phenolic content of 1125.4180 mgGAE/g while whole plant had the highest total flavonoid content with 1161.0340 mgGAE/g. The lowest concentration of half inhibition, IC₅₀ belonged to whole plant and leaves extracts which signified that both possess a good antioxidant activity. In conclusion, whole plant, leaves as well as stem of Physalis minima linn could be a potential source of natural antioxidant.